Selected individual differences as predictors of milk product consumption in a group of perimenopausal women in the light of health hazards - Gacek, Maria (Menopause Review/Przegląd Menopauzalny, 2013)
The aim of this study was to analyze the consumption frequency of dairy products depending on selected individual traits (level of self-efficacy, optimism, and satisfaction with life) in a group of perimenopausal women. The study, using the questionnaire for the assessment of food product consumption frequency, and psychological tests (GSES, LOT-R, SWLS), was conducted in a group of 320 women aged between 45 and 55. The Spearman’s coefficients of rank correlation and the Kruskal-Wallis test with the Dunn test for multiple comparisons were used for statistical analysis (p < 0.05). Statistical analysis revealed that the level of self-efficacy correlated positively with the consumption frequency of low-fat cottage cheese, kefir (p < 0.05), buttermilk and natural yoghurt (p < 0.01), and was inversely correlated with the consumption of high-fat milk and high-fat cottage cheese (p < 0.01). The level of optimism showed a positive correlation with the frequency of kefir and fruit yoghurt consumption (p < 0.05), and was inversely correlated with the consumption of high- and low-fat milk (p < 0.05) and high-fat cottage cheese (p < 0.01). An increased level of satisfaction with life was associated with a more frequent consumption of kefir (p < 0.05) and fruit yoghurt (p < 0.01), and with a lower consumption of high- and low-fat milk (p < 0.05) and high-fat cottage cheese (p < 0.01). The level of self-efficacy significantly influenced mean consumption frequency of high- (p < 0.0001) and low-fat milk (p < 0.05), high-fat cottage cheese, buttermilk, and natural (p < 0.0001) and fruit yoghurt (p < 0.01), and the levels of optimism and satisfaction with life exerted a significant effect on the frequency of consumption of high-fat milk, high-fat cottage cheese, and fruit yoghurt (p < 0.01). Overall, our study showed that the frequency of dairy product consumption among 45-55-year-old women is low and varies depending on the analyzed individual traits.